Automated monitoring of aquaponics with biofiltration system - Bracino, Amir A. (Animo Repository, 2023)
Aquaponics allows vegetables and fish to grow at the same time by using aquatic byproducts to provide at least 50% of the nutrients needed to sustain plant growth. This is made possible by the presence of beneficial microbial communities such as nitrifying bacteria. They can grow anywhere in the system but are mostly found in biofilters due to the large surface area they can provide. Consisting of two processes mechanical filtration and biological filtration, the biofiltration system is where water is received from the fishpond before it is sent to the hydroponic unit. Improving the conversion efficiency of biological filtration systems can address common water quality problems such as increased concentrations of ammonia and nitrites, accumulation of organic matter, and decreased levels of dissolved oxygen. Maintaining these water quality parameters contributes to the productivity of the aquaponics system and its subsystems. The aquaponics system designed is a pilot-scale model with two independent systems, control (with biofilter) and experimental (without biofilter). The media used in the biofilter is readily available and inexpensive gravel. An aeration system is installed in the biofilter to supply oxygen during its maturation phase which took about 2 months. To facilitate automatic monitoring of the physicochemical properties of water such as pH, temperature, dissolved oxygen, and turbidity, a centralized sensory chamber was built connected to each of the grow chambers and fish tanks. Ammonia, nitrite, and nitrate were tested by dropping solutions into water samples and comparing the developed color to a color chart. The pH, temperature, dissolved oxygen, and turbidity results fell outside the ideal ranges but are within the tolerable growing ranges. The system is operating at compromised parameters to cater to the growth and development of the fishes, plants, and nitrifying bacteria. The crop utilized in this study is mint (Mentha spicata). Results showed that the growth of mint in the experimental set up is faster as compared to the mint in the control set up which is attributed to the abundance of nitrate because of the presence of nitrifying bacteria in the biofilter. As for the fishes, Red Tilapia (Oreochromis aureus x Oreochromis mossambicus) was utilized. Tilapia were fed twice daily with fish pellets that are suitable to their current sizes. Results showed that the tilapia in the experimental set up grows at a faster rate as compared to the tilapia in the control set up. Overall, the performance of the experimental set up is more promising as compared to the control set up. The capital cost and the operating costs were also presented.